MOTHER’S CHARTCTERISTICS THAT AFFECT COMPLETENESS OF BASIC IMMUNIZATION OF TODDLERS AT MARYKE HEALTH CENTER LANGKAT DISTRICT - Ariescha, Putri Ayu Yessy; Ariani, Peny (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2024)
One effort to reduce morbidity and mortality rates in children is by providing immunizations. Immunization is an effective and efficient strategy in improving national health by preventing six deadly diseases, namely: tuberculosis, diptheria, pertussis, measles, tetanus and polio. Based on a preliminary survey observing several posyandu in the Bayu Muslimin country, data was obtained that 68% of babies received complete basic immunization compared to the national target of 95%. The aim of this research is to determine the relationship between maternal knowledge and attitudes and compliance with providing complete basic immunization to babies at the Maryke Community Health Center. The research design is descriptive correlative with a cross sectional study approach. The population in this study were all mothers who had babies aged 0-12 months. Sampling in this study used total sampling. The sample in this research was 40 people. The Chi-Square test results obtained a value of p = 0.001. This shows that there is a significant relationship between maternal knowledge and compliance with providing complete basic immunization to babies. As well as the Chi-Square test, the value of p = 0.000 was obtained, which shows that there is a significant relationship between attitude and maternal compliance in providing complete basic immunization for babies